Nano ceramic coating insulator for electric dust remover and preparation method of nano ceramic coating insulator

By using nano-ceramic coated insulators in electrostatic precipitators, the failure problems caused by condensation and dust adhesion in the insulators are solved, anti-condensation and anti-pollution flashover effects are achieved, and energy consumption and maintenance complexity are reduced.

CN119340046APending Publication Date: 2025-01-21FUJIAN LONGKING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411403162.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The insulators in the electro-dust collector are crawled, leakage and short-circuit failures caused by condensation and dust bonding, resulting in economic losses and equipment damage. The prior art relies on electric heaters and hot air purge, which has problems of high energy consumption and complex maintenance.

Method used

Using nano -ceramic coating insulators, through the water hate and anti -adhesive function of ceramic coatings, combined with the chemical bonds of nano ceramic coatings and insulators, to form the effect of anti -exposure and anti -flicker flash, reduce or cancel the electric heating device and hot air blowing Use.

Benefits of technology

The water vapor on the surface of the insulator does not form a form of water film, avoiding climbing and high -voltage breakdown. At the same time, the dust does not stick to form a pollution flash.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340046A_ABST
    Figure CN119340046A_ABST
Patent Text Reader

Abstract

The invention discloses a nano ceramic coating insulator for an electric dust remover and a preparation method of the nano ceramic coating insulator, and belongs to the technical field of flue gas pollutant treatment. According to the method, the nano ceramic coating is prepared, then the insulator body made of a ceramic material is subjected to degreasing, oil removal and acid pickling pretreatment, the surface of the insulator is coated with the nano ceramic coating, firm combination of the nano ceramic coating and the body is achieved through self-assembly (SAMs), and a nano ceramic coating structure is constructed; according to the nano ceramic coating insulator, the good hydrophobicity and the anti-sticking function of the ceramic coating structure and the firm combination of chemical bonds between the nano ceramic coating structure and the insulator body are utilized, so that water vapor on the surface of the insulator cannot form a sheet of water film, creepage and high-voltage breakdown are avoided, meanwhile, dust cannot be bonded to form pollution flashover, and the service life of the insulator is prolonged. Therefore, the anti-condensation and anti-pollution flashover effects of the insulator are achieved, and the operation of an electric heater and hot air blowing in the operation process is reduced or even canceled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flue gas pollutant treatment, and particularly relates to a nano ceramic coating insulator for an electric precipitator and a preparation method thereof. Background Art

[0002] In the power industry, since insulators are directly exposed to the dust-filled electric field, their anti-condensation performance is very poor. Electrical faults such as leakage, creepage, and short circuit are often caused by severe condensation and moisture on the surface of the insulator. The insulation failure, short-circuit shutdown, and equipment damage caused by this phenomenon have caused great economic losses. The main causes of dirty flashover are the adhesion of dust on the surface of the insulator and the condensation of water vapor. On the one hand, the fine dust in the flue gas of the electrostatic precipitator can easily enter the inside of the insulator and adsorb on the surface of the insulator, which can cause creepage on the surface of the insulator, making it impossible to increase the secondary voltage of the electrostatic precipitator, affecting the dust removal performance, and even causing a discharge short circuit. On the other hand, cold air will flow back into the insulation box and contact the insulator to cause condensation on the surface of the insulator. The condensation of the insulator will reduce the insulation strength of the insulator, causing the high-voltage part to discharge and break through the insulator to the ground, causing the insulator to be damaged, and affecting the dust removal efficiency of the electrostatic precipitator.

[0003] At present, the method to solve the flashover caused by condensation on insulators in the industry is usually to add heating devices to the internal space of the upper body of the electrostatic precipitator to heat its insulators, increase the power or number of heating devices to increase and maintain the temperature in the insulation box, or use dry spiral wind to blow the insulators to ensure that the insulators are dry and do not condense, so as to achieve the purpose of preventing flashover on insulators. In thermal power, cement and other industries, electrostatic precipitators are generally equipped with insulation boxes, and electric heaters are used to heat their insulators (heated to 110-130°C), or dry spiral wind is used to blow the insulators.

[0004] For example, a Chinese patent with publication number CN101468333A and application date of December 24, 2007 discloses an anti-condensation insulator, which comprises an insulator body (1); a heating device assembly chamber (2) is provided in the insulator body (1); and a heating device (3) is provided in the heating device assembly chamber (2). In the present invention, a thermocouple temperature control element (4) can also be provided in the heating device assembly chamber (2), and the temperature of the insulator is increased by installing a heating device inside the insulator, thereby achieving the purpose of anti-condensation.

[0005] However, due to the relatively large area of ​​the existing insulation box, the heat energy cannot be well concentrated on the insulator. In order to maintain the temperature of the insulation box, a large number of electric heaters are needed, which consumes a lot of electricity. The power of the heater equipped on each insulator is 1.5KW. The electricity cost of a single electrostatic precipitator to prevent flashover reaches 2 to 3 million yuan per year. The hot air blowing system has complex process and high maintenance requirements. The uneven distribution of hot air reduces reliability and the insulator is also likely to explode. Therefore, it causes great loss and waste of both electricity and heat energy.

[0006] A Chinese patent with publication number CN104240872A and application date of September 26, 2014 discloses a method for preventing pollution flashover of insulators of electrostatic precipitators, by coating the surface of the insulator with a vulcanized silicone rubber coating and utilizing the hydrophobicity of silicone rubber to prevent condensation and pollution flashover of the insulator. Silicone rubber RTV coating is a common solution for preventing pollution flashover of external insulation components of power transmission and transformation in the power industry, but it is not applicable to the electrostatic precipitator industry. The main reason is that the operating temperature of insulators for power transmission and transformation is the natural ambient temperature, which is relatively low, while the operating temperature of electrostatic precipitator equipment is usually greater than 100°C or even higher. Silicone rubber materials age severely at high temperatures and cannot be used for a long time. On the other hand, the hydrophobic angle of silicone rubber is only more than ninety degrees, and the hydrophobic effect is average, making it difficult to completely prevent the occurrence of condensation and pollution flashover.

[0007] At present, the problem of equipment failure caused by creepage and high-voltage breakdown in the actual operation of electrostatic precipitators has attracted increasing attention. Therefore, there is an urgent need to design an insulator with good anti-condensation and anti-pollution flashover performance, which can replace the effect of electric heaters or hot air blowing, effectively reduce operating costs and maintenance costs, and maintain good insulation performance, and has the characteristics of corrosion resistance, thermal stability and wear resistance, thereby providing a strong guarantee for the long-term safe and stable operation of electrostatic precipitators. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a nano-ceramic coated insulator for an electrostatic precipitator and a preparation method thereof. The nano-ceramic coated insulator utilizes the good hydrophobicity and anti-sticking function of the ceramic coating structure, and the strong combination of chemical bonds between the nano-ceramic coating structure and the insulator body, so that water vapor on the surface of the insulator will not form a water film, thereby avoiding creepage and high-voltage breakdown. At the same time, dust will not adhere to form flashover, so that the insulator can achieve anti-condensation and anti-flashover effects, and reduce or even eliminate the operation of electric heaters and hot air blowing during operation.

[0009] The technical solution of the present invention is as follows:

[0010] One of the purposes of the present invention is to provide a method for preparing a nano ceramic coating insulator for an electrostatic precipitator, comprising the following steps:

[0011] S1. Select an insulator body made of ceramic material, and perform degreasing, deoiling and pickling pretreatment on it;

[0012] S2, uniformly coating the inner and outer surfaces of the insulator with a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent;

[0013] S3. The insulator after the coating operation is subjected to low temperature curing to construct a nano-ceramic coating structure, thereby obtaining an insulator with a nano-ceramic coating.

[0014] Furthermore, the degreasing and oil removal treatment in S1 is to immerse the insulator in a degreasing agent at 60-70° C. for 6-8 minutes; the pickling treatment is to immerse the insulator in a 10% sulfuric acid solution, stir for 1-2 hours, and then let it stand for 8-12 hours.

[0015] Furthermore, the nano-ceramic particles in S2 include nano-aluminum oxide particles, nano-titanium oxide particles, nano-zirconium oxide particles and nano-silicon oxide particles, wherein the mass ratio of the nano-silicon oxide particles to the other nano-particles is 1:1 to 8:1.

[0016] Furthermore, the colloidal solvent in S2 includes anhydrous ethanol, n-heptane, xylene and naphtha in a mass ratio of 4:2:3:1 to 3:2:2:1.

[0017] Furthermore, the mass ratio of the nano ceramic particles to the colloidal solvent in S2 is 1:5, and the two are fully stirred, mixed and hydrolyzed for 2 to 3 hours to obtain the nano ceramic coating.

[0018] Furthermore, the coating process in S2 is carried out within 24 hours after the pretreatment is completed.

[0019] Furthermore, the coating method in S2 is a spraying process or a brushing process;

[0020] The spraying process parameters are as follows: spray room temperature is 25°C, humidity condition is 60% RH, spray pressure is 4.5 bar, gun distance is 15 cm, spray flow rate is 60 CC / min;

[0021] The brushing process parameters are as follows: Use a fine-bristled brush to evenly apply nano-ceramic particles to the inner and outer surfaces of the insulator using a cross-cross method to ensure that there is no dew point, and apply at least two times.

[0022] Furthermore, the low temperature curing condition in S3 is baking at 90-120° C. for 20-40 min.

[0023] A second object of the present invention is to provide a nano-ceramic coating insulator for an electrostatic precipitator.

[0024] Furthermore, the nano ceramic coating has a thickness of 10 to 50 μm.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] 1. The present invention designs for the first time a nano-ceramic coating insulator for an electrostatic precipitator. The nano-ceramic coating insulator utilizes the good hydrophobicity and anti-sticking function of the ceramic coating structure, as well as the strong combination of chemical bonds between the nano-ceramic coating structure and the insulator body, so that water vapor on the surface of the insulator will not form a water film, thereby avoiding creepage and high-voltage breakdown. At the same time, dust will not adhere to form pollution flashover, so that the insulator can achieve anti-condensation and anti-pollution flashover effects, and reduce or even eliminate the operation of electric heaters and hot air blowing during operation.

[0027] 2. Compared with the prior art, the nano-ceramic coating disclosed in the present invention has good hydrophobicity and can provide a self-aggregation effect similar to that of lotus leaves, so that the water vapor on the surface of the insulator often forms isolated water droplets rather than a water film, thereby improving the anti-pollution flashover capability of the insulator. At the same time, the nano-ceramic coating also has excellent dust resistance and easy-to-clean performance. When the dust reaches a small thickness, it will peel off under the action of its own weight and cannot continue to accumulate on the insulator, eventually forming a self-balance of dust adhesion-peeling-re-adhesion-re-peeling.

[0028] 3. The present invention realizes a firm combination of the nano-ceramic coating and the insulator body through self-assembly (SAMs), and forms a dense coating with a nanostructure on the surface of the body. The insulator as a whole has the characteristics of corrosion resistance, thermal stability and wear resistance, and can withstand the erosion of dust for a long time under high temperature conditions, and has stable performance and maintains good insulation performance. In addition, the nano-ceramic coating can replace the technical effects of electric heaters and hot air blowing, so it can reduce or even eliminate the operation of electric heaters and hot air blowing, reduce heaters and related cables, control devices and other equipment, save a lot of equipment investment and power consumption in the operation stage, and greatly reduce operating costs. At the same time, it can also reduce related equipment maintenance and repair work, eliminate accidents such as shutdowns caused by flashover damage to insulators caused by heating equipment failures, and increase the stability and reliability of equipment operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM cross-sectional morphology of the nano-ceramic coating of the present invention;

[0030] Figure 2 The SEM surface morphology of the nano-ceramic coating of the present invention;

[0031] Figure 3 This is a test result diagram of the hydrophobicity of the nano-ceramic coating insulator of the present invention;

[0032] Figure 4 This is a comparison chart of the dust adhesion experiment on the inner wall of the insulator sprayed with and not sprayed with the nano-ceramic coating of the present invention. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. The given embodiments are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources;

[0035] The quantitative tests in the following examples were repeated three times, and the results were averaged.

[0036] The experimental methods in the following embodiments are conventional methods unless otherwise specified.

[0037] Example 1

[0038] This embodiment provides a method for preparing a nano-ceramic coating insulator, comprising the following steps:

[0039] S1, preparing nano ceramic particles consisting of 500 g of nano aluminum oxide particles, 25 g of nano titanium oxide particles, 15 g of nano zirconium oxide particles and 60 g of nano silicon oxide particles;

[0040] S2, adding a colloidal solvent consisting of 1200 g of anhydrous ethanol, 600 g of n-heptane, 900 g of xylene and 300 g of naphtha to the prepared nano-ceramic particles, stirring and mixing for 2 hours, and then hydrolyzing to obtain a nano-ceramic coating and a colloidal solvent;

[0041] S3, immerse the ceramic insulator body in a first degreasing tank at 65°C for 6 minutes, and then immerse it in a second degreasing tank for another 3 minutes, wherein the tank liquid in the degreasing tank is a 50g / L degreasing agent;

[0042] S4. After degreasing and deoiling, immerse the insulator in a 10% sulfuric acid solution and stir for 2 hours, then let it stand for 8 hours, and then go through two water washing processes, washing with pure water and drying, and drying thoroughly;

[0043] S5. Within 24 hours after the pretreatment is completed, a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent is uniformly coated on the inner and outer surfaces of the insulator by a spraying process;

[0044] The spraying process parameters are as follows: spray room temperature is 25°C, humidity condition is 60% RH, spray pressure is 4.5 bar, gun distance is 15 cm, spray flow rate is 60 CC / min;

[0045] S6. The insulator after the coating operation is baked at 90° C. for 40 minutes, and low-temperature cured to construct a nano-ceramic coating structure with a film thickness of 15 μm, thereby obtaining an insulator with a nano-ceramic coating.

[0046] Example 2

[0047] This embodiment provides a method for preparing a nano-ceramic coating insulator, comprising the following steps:

[0048] S1, preparing nano ceramic particles consisting of 800 g of nano aluminum oxide particles, 25 g of nano titanium oxide particles, 15 g of nano zirconium oxide particles and 60 g of nano silicon oxide particles;

[0049] S2, adding a colloidal solvent consisting of 1800 g of anhydrous ethanol, 900 g of n-heptane, 1350 g of xylene and 450 g of naphtha to the prepared nano-ceramic particles, stirring and mixing for 3 hours, and then hydrolyzing to obtain a nano-ceramic coating;

[0050] S3, immerse the ceramic insulator body in a first degreasing tank at 65°C for 6 minutes, and then immerse it in a second degreasing tank for another 3 minutes, wherein the tank liquid in the degreasing tank is a 50g / L degreasing agent;

[0051] S4. After degreasing and deoiling, immerse the insulator in a 10% sulfuric acid solution and stir for 1.5 hours, then let it stand for 10 hours, and then go through two water washing processes, washing with pure water and drying, and drying thoroughly;

[0052] S5. Within 24 hours after the pretreatment is completed, a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent is uniformly coated on the inner and outer surfaces of the insulator by a spraying process;

[0053] The spraying process parameters are as follows: spray room temperature is 25°C, humidity condition is 60% RH, spray pressure is 4.5 bar, gun distance is 15 cm, spray flow rate is 60 CC / min;

[0054] S6. The insulator after the coating operation is baked at 120° C. for 40 minutes, and low-temperature cured to construct a nano-ceramic coating structure with a film thickness of 50 μm, thereby obtaining an insulator with a nano-ceramic coating.

[0055] Example 3

[0056] This embodiment provides a method for preparing a nano-ceramic coating insulator, comprising the following steps:

[0057] S1, preparing nano ceramic particles consisting of 100 g of nano aluminum oxide particles, 25 g of nano titanium oxide particles, 15 g of nano zirconium oxide particles and 60 g of nano silicon oxide particles;

[0058] S2, adding a colloidal solvent consisting of 375g of anhydrous ethanol, 250g of n-heptane, 250g of xylene and 125g of naphtha to the prepared nano-ceramic particles, stirring and mixing for 2.5h, and then hydrolyzing to obtain a nano-ceramic coating;

[0059] S3, immerse the ceramic insulator body in a first degreasing tank at 65°C for 6 minutes, and then immerse it in a second degreasing tank for another 3 minutes, wherein the tank liquid in the degreasing tank is a 50g / L degreasing agent;

[0060] S4. After degreasing and deoiling, immerse the insulator in a 10% sulfuric acid solution and stir for 1 hour, then let it stand for 12 hours, and then perform two water washing processes, wash with pure water and then dry it thoroughly;

[0061] S5. Within 24 hours after the pretreatment is completed, a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent is uniformly coated on the inner and outer surfaces of the insulator by a spraying process;

[0062] The spraying process parameters are as follows: spray room temperature is 25°C, humidity condition is 60% RH, spray pressure is 4.5 bar, gun distance is 15 cm, spray flow rate is 60 CC / min;

[0063] S6. The insulator after the coating operation is baked at 120° C. for 30 minutes, and low-temperature cured to construct a nano-ceramic coating structure with a film thickness of 30 μm, thereby obtaining an insulator with a nano-ceramic coating.

[0064] Example 4

[0065] This embodiment provides a method for preparing a ceramic coated insulator, comprising the following steps:

[0066] S1, preparing nano ceramic particles consisting of 300 g of nano aluminum oxide particles, 25 g of nano titanium oxide particles, 15 g of nano zirconium oxide particles and 60 g of nano silicon oxide particles;

[0067] S2, adding a colloidal solvent consisting of 750 g of anhydrous ethanol, 500 g of n-heptane, 500 g of xylene and 250 g of naphtha to the prepared nano-ceramic particles, stirring and mixing for 2.5 hours, and then hydrolyzing to obtain a nano-ceramic coating;

[0068] S3, immerse the ceramic insulator body in a first degreasing tank at 65°C for 6 minutes, and then immerse it in a second degreasing tank for another 3 minutes, wherein the tank liquid in the degreasing tank is a 50g / L degreasing agent;

[0069] S4. After degreasing and deoiling, immerse the insulator in a 10% sulfuric acid solution and stir for 1 hour, then let it stand for 12 hours, and then perform two water washing processes, wash with pure water and then dry it thoroughly;

[0070] S5. Within 24 hours after the pretreatment is completed, a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent is uniformly applied on the inner and outer surfaces of the insulator by a brush coating process;

[0071] The brushing process parameters are as follows: Use a fine-bristled brush to evenly apply the nano-ceramic particles to the inner and outer surfaces of the insulator using a cross-cross method, ensuring that there is no dew point, and repeat the construction 3 times.

[0072] S6. The insulator after the coating operation is baked at 100° C. for 20 minutes, and low-temperature cured to construct a nano-ceramic coating structure with a film thickness of 35 μm, thereby obtaining an insulator with a nano-ceramic coating.

[0073] Performance Testing

[0074] 1. Hydrophobic and anti-stick performance test

[0075] The hydrophobicity of the nano ceramic coating insulator prepared in Example 1 was tested. Figure 3 As shown, the prepared insulator exhibits excellent anti-stick and hydrophobic properties: the coating adhesion is grade 0 according to the ISO adhesion test standard; the hydrophobic angle of the coating is 110°, and it has good hydrophobic and anti-stick properties.

[0076] 2. Corrosion resistance test

[0077] The nano-ceramic coating insulators prepared in Example 1 were tested using the neutral salt spray test (NSS) test standard. The coatings of multiple groups of samples did not show any changes after 1500 hours, showing excellent corrosion resistance.

[0078] 2. Dust adhesion test inside insulator

[0079] Ceramic insulators of the same size as in Example 1 were selected as the control group for pretreatment. The specific implementation steps were the same as in Example 1, except that the control group insulators did not construct a nano-ceramic coating structure. The nano-ceramic coating insulators prepared in Example 1 and the control group insulators were placed in an operating environment with the same dust conditions, and the inner wall conditions were observed after running for the same period of time.

[0080] Test results such as Figure 4As shown, from the dust adhesion test photos of the inner wall of the insulator of the control group, it can be seen that a thick layer of fine dust adheres to the inner wall, and the dust layer is dense and has no peeling phenomenon. As time goes by, the dust thickness will become thicker and thicker. If condensation occurs at that time, the adhered dust will form a layer of hardened dust similar to "cement" inside. When the dust layer reaches a certain thickness, the insulator will be punctured under the action of high voltage, causing the risk of explosion; for the nano-ceramic coated insulator prepared in Example 1, the dust will peel off under the action of its own weight after reaching a relatively small thickness, and cannot continue to accumulate on the inner wall of the insulator, effectively reducing the dust adhesion.

[0081] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a nano ceramic coating insulator for an electric precipitator, characterized in that: The following steps are involved: S1. Select an insulator body made of ceramic material, and perform degreasing, deoiling and pickling pretreatment on it; S2, uniformly coating the inner and outer surfaces of the insulator with a nano-ceramic coating composed of nano-ceramic particles and a colloidal solvent; S3. The insulator after the coating operation is subjected to low temperature curing to construct a nano-ceramic coating structure, thereby obtaining an insulator with a nano-ceramic coating.

2. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The degreasing and oil removal treatment in S1 is to immerse the insulator in a degreasing agent at 60-70° C. for 6-8 minutes; the pickling treatment is to immerse the insulator in a 10% sulfuric acid solution, stir for 1-2 hours, and then let it stand for 8-12 hours.

3. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The nano ceramic particles in S2 include nano aluminum oxide particles, nano titanium oxide particles, nano zirconium oxide particles and nano silicon oxide particles, wherein the mass ratio of the nano silicon oxide particles to other nano particles is 1:1 to 8:

1.

4. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The colloidal solvent in S2 includes anhydrous ethanol, n-heptane, xylene and naphtha in a mass ratio of 4:2:3:1 to 3:2:2:

1.

5. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The mass ratio of the nano ceramic particles to the colloidal solvent in S2 is 1:5, and the two are fully stirred, mixed and hydrolyzed for 2 to 3 hours to obtain the nano ceramic coating.

6. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The coating process in S2 is carried out within 24 hours after the pretreatment is completed.

7. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The coating method in S2 is a spraying process or a brushing process; The spraying process parameters are as follows: spray room temperature is 25°C, humidity condition is 60% RH, spray pressure is 4.5 bar, gun distance is 15 cm, spray flow rate is 60 CC / min; The brushing process parameters are as follows: Use a fine-bristled brush to evenly apply nano-ceramic particles to the inner and outer surfaces of the insulator using a cross-cross method to ensure that there is no dew point, and apply at least two times.

8. The method for preparing a nano ceramic coating insulator for an electrostatic precipitator according to claim 1, characterized in that: The low temperature curing condition in S3 is baking at 90-120° C. for 20-40 minutes.

9. A nano ceramic coating insulator for an electrostatic precipitator prepared by the preparation method according to any one of claims 1 to 8.

10. The nano ceramic coating insulator for an electric precipitator according to claim 9, characterized in that: The thickness of the nano ceramic coating is 10 to 50 μm.

Citation Information

Patent Citations

  • Anti-dewing insulator

    CN101468333A

  • Pollution flashover prevention method for insulators of electrostatic precipitators

    CN104240872A